DEN SIAMESISKE SAMLING I EBELTOFT - Funder, Torkil (Tidsskriftet Antropologi, 2001)
Rasmus Havmøller did the Siamese Collection during the twenty years he was a forester in Siam. In 1940, after returning to his native Ebeltoft, Havmøller donated his collection to the local museum. The objects were displayed according to his wishes and remain in much the same arrangement today after a recent conservation of all 6-800 items. The article argues that the collection’s musealogical interest is to be found in the character of the presentation of the objects. In three small rooms, filled to the brim, we meet objects gathered by one person according to his interests. Hunting trophies, specimens in spirits, utensils, ceramics, stone tools etc., mostly from Siam. The moment the gathered objects left Siam they obtained a quality of completion, became a whole, so to speak, with no additions possible. This was the number of statements or testimonies of a foreign reality that chance and personality had brought together: A true collection. Accordingly, all objects are presented as individuals of equal im-portance. Most are provided with a factual, very brief text: “Gold from Bang Sapan, northern Siam”, “536 Gecco. Very common in houses, living from insects. This specimen of medium size”, “Fruit from the rain forest”. One meets the objects as single and free individuals, which speak only of themselves. Wider contexts like Siam, or the ingenuity of the biological world, or the life of an employee during colonial times must be perceived by the visitors themselves. This way of presenting objects stands in great contrast to many present day exhibitions. These often consist of objects brought together from many different sources in order to represent an academic category which is common to them. Such constructions hold numerous rewards perhaps for communicating cultural history, but in disregarding the original context, setting, and aura of the participating exhibits, they leave out important primary information and remain useful, but artificial. The object and its original background thus may become a prisoner of the carefully lit and coloured showcase in which it is displayed, as well as becoming a hostage of the educational, lengthy text that accompanies it. To apply the simple, unconsciously adopted principles of the 1940-displays in Ebeltoft – one object, one text, simple appearance, no sermons – to a modern exhibition is possible of course, but it may meet with numerous difficulties. Major limits are omitting what is technically possible, and not narrating all that one knows, reserving this knowledge for the catalogue. Thus, the exhibit under discussion allows the objects to appear as they were while found, collected, and still around us as parts of a whole, but basically as particulars.